2019
DOI: 10.3832/ifor2777-012
|View full text |Cite
|
Sign up to set email alerts
|

Genetic control of intra-annual height growth in 6-year-old Norway spruce progenies in Latvia

Abstract: Biogeosciences and Forestry Biogeosciences and Forestry Genetic control of intra-annual height growth in 6-year-old Norway spruce progenies in Latvia Roberts Matisons (1) , Pauls Zeltiņš (1) , Darius Danusevičius (2) , Baiba Džeriņa (1) , Iveta Desaine (1) , Āris Jansons (1) Coupling growth with periods of favourable weather conditions minimizes risks of frost damage and maximizes annual height increment. The phenology of the formation of height increment is therefore a trait related to the adaptability of tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
(43 reference statements)
0
1
0
Order By: Relevance
“…In a common garden experiment of P. brutia established in the Mediterranean region of Turkey, seed sources from the middle elevation distribution of the species were superior for growth and also produced a higher number of flushes than the seed sources from the peripheral distribution . Jayawickrama et al (1998) reported seed source variation in the date of cessation of annual height growth and a moderately strong correlation with total height growth, such that coastal seed sources tended to grow longer in the year and produce taller trees in Pinus taeda L. Shoot elongation patterns of pines could be adaptive, controlled by multiple environmental and genetic factors (Girard et al 2012;Hover et al 2017;Matisons et al 2019).…”
mentioning
confidence: 99%
“…In a common garden experiment of P. brutia established in the Mediterranean region of Turkey, seed sources from the middle elevation distribution of the species were superior for growth and also produced a higher number of flushes than the seed sources from the peripheral distribution . Jayawickrama et al (1998) reported seed source variation in the date of cessation of annual height growth and a moderately strong correlation with total height growth, such that coastal seed sources tended to grow longer in the year and produce taller trees in Pinus taeda L. Shoot elongation patterns of pines could be adaptive, controlled by multiple environmental and genetic factors (Girard et al 2012;Hover et al 2017;Matisons et al 2019).…”
mentioning
confidence: 99%